Respuesta :

2x^2 + 4x + 3 – 4x^2 +2x +3 = -2x²   +6x  +6
Answer D

Answer:  The correct option is

(D) [tex]-2x^2+6x+6.[/tex]

Step-by-step explanation:  We are given to subtract the following polynomials :

[tex]P=(2x^2+4x+3)-(4x^2-2x-3)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]

To subtract the given polynomials, we need to subtract the coefficients of the terms with same powers of the unknown variable x.

From (i), we get

[tex]P\\\\=(2x^2+4x+3)-(4x^2-2x-3)\\\\=2x^2+4x+3-4x^2+2x+3\\\\=(2-4)x^2+(4+2)x+(3+3)\\\\=-2x^2+6x+6.[/tex]

Thus, the required resulting polynomial is [tex]-2x^2+6x+6.[/tex]

Option (D) is CORRECT.